Formaldehyde Synthesis Over Foam Metal Catalysts - Pestryakov, Alexey; Lunin, Valerii (Current Organic Synthesis, 2017)
Background: The foam materials have a number of interesting properties which may be used in processes of high temperature alcohol partial oxidation to aldehydes and ketones. Foam materials have uniform cellular structure with isotropy of mechanical and fluidodynamic properties: an average diameter of the elementary cell - 0.5-5.0m; porosity - 80-98%; volume density - 0.1-0.5 g/cm3. Objective: The aim of the present paper is comparative investigation of physicochemical and catalytic properties of Cu, Ag and Au catalysts supported on foam ceramics in the process of partial oxidation of methanol to formaldehyde. Method: Catalytic tests in methanol oxidation at T=550-650 °C. Transmission electron microscopy, adsorption measurements for m testing specific surface area. Results and Conclusion: Catalysts based on Ag, Cu and Au supported on foam ceramics are promising for usage in the processes of alcohol selective oxidation due to their high catalytic, mechanical and gas-dynamic properties. Among these metals Ag catalysts are the most effective; the catalytic characteristics of the Cu samples are much worse. This is caused by the formation of some numbers of Cu2+ ions favoring deep oxidation of alcohols. The activity of gold catalysts (methanol conversion, formaldehyde yield) is substantially lower than those of Ag and Cu samples because of poor oxidizability of gold. However, the selectivity of Au catalysts exceeds the one of Cu samples due to higher stability of active M+ ions.
Keywords: copper